Severe Acute Respiratory Syndrome Coronavirus 2 Infection Among Healthcare Workers in South Africa: A Longitudinal Cohort Study - Nunes, Marta C; Baillie, Vicky L; Kwatra, Gaurav; Bhikha, Sutika; Verwey, Charl; Menezes, Colin; Cutland, Clare L; Moore, David P; Dangor, Ziyaad; Adam, Yasmin; Mathivha, Rudo; Velaphi, Sithembiso C; et al. (Clinical infectious diseases, 2021)
Abstract From April to September 2020, we investigated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in a cohort of 396 healthcare workers (HCWs) from 5 departments at Chris Hani Baragwanath Hospital, South Africa. Overall, 34.6% of HCWs had polymerase chain reaction–confirmed SARS-CoV-2 infection (132.1 [95% confidence interval, 111.8–156.2] infections per 1000 person-months); an additional 27 infections were identified by serology. HCWs in the internal medicine department had the highest rate of infection (61.7%). Among polymerase chain reaction–confirmed cases, 10.4% remained asymptomatic, 30.4% were presymptomatic, and 59.3% were symptomatic.